Study on Identification and Extraction of Adulterants from Herbal Medicines - Sreya C. S.; Chauhan, Amit; Varsha R.; Xavier, Fr. Jobi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
In modern time, usage of herbal medicines has increased all over the world. Herbal medicines are use for treatment of primary health needs and conventional treatment too. Due to increased demand of these medicines, maniac people have started production of adulterants/ inappropriate chemical properties/ low grade drugs in products. In this concern, examination including, chemical tests, analytical tests, phytochemicals screening tests are performed to determine the purity of products, quantitative analysis of heavy metals, presence of drug. This chapter is mainly focused on the implementation of various analytical techniques i.e. HP-TLC, FTIR etc. for identification of derivatization of adulterants from herbal drugs. Extracted adulterants from these herbal medicines include, guanine, flavonoids, alcohol ferric chloride etc. were attained.